Effect of nectar pillaging by native stingless bees (Hymenoptera: Apidae) in the abscission of flowers of Bougainvillea spectabilis Willd. (Nyctaginaceae) - doi: 10.4025/actascibiolsci.v33i4.8191 - Rodrigo Aranda; Gisele Catian; Paulo Alexandre Bogiani; Igor Inforzato (Acta Scientiarum: Biological Sciences, 2011)
This study had as objective to evaluate whether the pillaging activity by native bees influences floral abscission. Samples were collected in ten individuals of Bougainvillea spectabilis. In the period between May 4 and June 1st, 2009, 2,874 flowers were collected on the ground and 2,895 from the plants, with three-day intervals between each collection and a total of 10 repetitions in each plant. We measured the total of closed flowers, open flowers, robbed flowers, normal flowers, open robbed flowers and non-robber open flowers, in both soil and plant. For the statistical analysis, the T-test was used to see whether there was a difference between the averages obtained from the evaluated characteristics between the soil flowers and plant flowers. Simple linear regression was used to see whether there was a relationship between the closed flowers and robbed closed flowers found on the ground and open flowers and non-robbed open flowers in the plant. There were significant differences regarding all variables measured between soil and plant. A correlation was found at both closed flowers and robbed closed flowers found on the ground and open flowers and non-robbed open flowers in the plant.